Evaluation of productive parameters of crossbred cattle finished in feedlot fed different diets with grain corn - Ragazzi, Fernanda; de Oliveira Machado, Acácia; Pimentel de Andrade, Mateus; de Sousa Rego, Ramon (Pubvet, 2019)
The objective of the present experiment was to evaluate the influence of maize grain supply on animal performance of beef cattle in feedlot system to evaluate the average weight gain (ADG - kg/day, hot carcass weight (HCW) and hot carcass dressing (HCD, %). Twenty-five crossbred cattle in finished for 65 days, separated according to feeding, sex, castrated or bulls, comprising four different treatments: T1: 10 bulls fed a restrictive grain corn diet; T2: 4 bulls, fed on corn, forage and CT600, T3: 5 steers fed grain corn, forage and protein, and T4 5 cows fed corn, forage and protein. The T1 group presented higher values of ADG (1.32 kg/day), HCW (113.13 kg) and HCD (50.42%). The use of maize grain feed is efficient for bulls even in SRD breeds in feedlot, presenting satisfactory results in productive income.
Keywords: crossbred cattle; feedlot; whole grain